Ergonomics Risk Assessment of Musculoskeletal Disorders Related to Patient Transfer Operation among Hospital Nurses Using PTAI Technique - Abedini R; Choobineh A; Hasanzadeh J (Iran University of Medical Sciences, 2013)
Background & Aims: Nursing staff suffer from work-related musculoskeletal disorders (WMSDs) more than other health care workers and patient handling is a main risk factor in the occurrence of these disorders. The purpose of this study was to assess the risk of musculoskeletal disorders due to patient handling using PTAI technique among hospital nurses working in hospitals affiliated to Shiraz University of Medical Sciences (SUMS).   Material & Methods: This cross-sectional study was conducted among 400 randomly selected nurses from 75 wards of 11 hospitals affiliated to SUMS. Data was collected by demographic and Nordic musculoskeletal disorders questionnaires and PTAI index checklist. Statistical analysis was performed using SPSS (v 16.). Chi-square test was applied to examine the difference between MSDs prevalence in different levels of PTAI index. Odds ratio was also calculated for each level of PTAI index.   Results: The mean score of age and job tenure of subjects was 30.76±6.44 and 6.92±5.75 years respectively. Prevalence rate of MSDs among the subjects was 88.2%. The results of PTAI index assessment revealed that 4% of subjects were at risk level 1, 8.5% at risk level 2 and 87.5% at risk level 3. The results indicated that PTAI index score was significantly associated with musculoskeletal disorders occurrence (p<0.001).  Conclusion: According to the findings, PTAI is an appropriate tool for musculoskeletal disorders risk identification and assessment due to patient handling in nursing personnel.   Received: 2 Apr 2013   Accepted: 10 Jun 2013